Real-time Frame Buffer Implementation based on External Memory using FPGA - Davutoğlu, Doğancan (Elsevier, 2018)
In this paper, design of a real-time video frame buffer with an external memory interface is proposed. In addition, simulation and implementation processes of the design is described. The mentioned system is able to buffer video signals up to 1920×1080 full-HD resolution at 60 Hz frame rate. The memory interface is designed based on an external SDRAM memory and supports burst read/write operations. Input video resolution, video buffer size on memory and burst size of the memory interface are user defined and can be configured.
Keywords: Real-time; field programmable gate arrays; memory interface; video frame buffer